Sistem Ekonomi Pancasila Sebagai Landasan Ketahanan Ekonomi Indonesia dalam Perspektif Filsafat Ilmu - Lindiasari, Palupi (Jurnal Kajian Stratejik Ketahanan Nasional, 2018)
This article aims to analyze the fundamental of the Pancasila economic system as a foundation for the resilience of the Indonesian economy in the perspective of National Resilience. The study method uses a philosophy of science approach through the ontological dimension. There are three elements to determine the essence of the Pancasila economy, namely: macroeconomics, microeconomics and literal meaning. In macro terms, Pancasila economic system is explained in the UUD 1945 chapter 33 verses 1 to 5, whose essence consists of two elements (dualism) in defining welfare, namely material (outwardly) and inner (spiritual) which must be achieved equally through Gotong Royong. Literally, the fundamental of the Pancasila economy consists of economic philosophy and Pancasila philosophy. The economy explain the needs of human life (individual households, families, and countries), while Pancasila is representative of the godly element of man. Therefore the Pancasila economic system is a system of household management (material) by godless people (prioritizing intelligence). The results of the study of micro-economic elements, defining godless humans as humans who run the Pancasila economy through the components of the human brain, namely the neo-cortex which describes an awareness of each individual in behaving as a godly human. It’s mean that human behavior is compassionate which is implemented with a caring attitude or better known as mutual cooperation (Gotong Royong). The Pancasila economic system as the foundation of Indonesia's economic resilience is able to explain the strength or resilience of the state in maintaining economic stability which consists of two elements namely economic soft skills and economic hard skills. Both of these powers aim to realize inner and outer prosperity for all people without exception with equitable growth through mutual cooperation (Gotong Royong).